Pengaruh Metode Storytelling Terhadap Peningkatan Kemampuan Berbicara Anak Usia 5-6 Tahun Di TK Pembina HKBP Tarutung - Lediman Br Samosir; Julita Herawati P; Rotua Samosir (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The purpose of this study was to determine the effect of the Storytelling method on improving the speaking ability of children aged 5-6 years at TK Pembina HKBP Tarutung. The background of this research is the low speaking ability of children in HKBP Tarutung Pembina Kindergarten. The method used in this research is a quantitative research method of ipre-experimental idesign type, namely iOne iShot iCase iStudy. The population was all children aged 5-6 years at TK Pembina HKBP Tarutung which amounted to 94 people and a sample of 30 children was determined with nonprobability sampling technique, namely purposive sampling. Data were collected with 30 positive closed questionnaire items. The results of data analysis show that there is a positive and significant effect of the Storytelling method on improving the speaking ability of children aged 5-6 years at TK Pembina HKBP Tarutung: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.489 > rtable (a=0.05, n=30) = 0.361 thus it is known that there is a positive relationship between variable X and variable Y. b) significant relationship test obtained tcount = 2.968 > ttable (a=0.05, dk=n-2=28) = 2.048 thus there is a significant relationship between variable X and variable Y. c) regression determination coefficient test (r2) = 23.9%. 2) Effect test: Regression equation test, obtained regression equation Y ̂="23", "08"+0.48X. Thus Ha is accepted and H0 is rejected.